MITIGATION OF PROFIT MANIPULATION OF REAL ACTIVITIES WITH EFFECTIVENESS OF INTERNAL GOVERNANCE STUDY ON PUBLIC COMPANIES IN INDONESIA - Carolyn Lukita Sembiring; Joicenda Nahumury (Universitas Airlangga, 2018)
This study aims to examine the effectiveness of internal governance to mitigate real activity earnings manipulation. Real activity profit manipulation as the dependent variable is measured in three proxies, namely sales activity manipulation (Abnormal CFO), production cost manipulation (Abnormal Production), and discretionary cost manipulation (Abnormal Discreationer) based on Roychowdhury, 2006). While the independent variable is internal governance, which is still relatively little researched but in several studies it has been shown to reduce real earnings management, this study measures internal governance based on Chen et al., (2016). This study also examines other variables as moderating variables, namely the control of an independent board of commissioners and institutional ownership which are thought to strengthen the effectiveness of internal governance in mitigating earnings manipulation. The data analysis technique used is multiple linear regression. This study succeeded in providing evidence that internal governance is able to mitigate earnings manipulation by managers. In addition, this study also provides support that institutional ownership and independent board of commissioners can moderate the influence between internal governance and real earnings management. The results of this study can add references to real earnings management mitigation and also as one of the considerations for long-term investment decisions in the capital market for investors.